2017
DOI: 10.3390/pharmacy5040066
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Hospital Pharmacists’ Job Satisfaction in Romanian Hospitals

Abstract: Aim: The purpose of this study is to identify the level of job satisfaction among hospital pharmacists in Romania in relation to environmental, socio-demographic, and individual factors. Material and Methods: Seventy-eight hospital pharmacists were included in the research. The Job Satisfaction Scale was used to measure the level of satisfaction with their current jobs, and the TAS-20 was used to evaluate emotional experience and awareness. Additionally, 12 items were formulated in order to identify the reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
2
14
1
1
Order By: Relevance
“…While pharmacists in New Zealand and Romania emphasized the importance of a higher salary as an important motivator, the pharmacists in Australia and the USA valued task assignment based on one’s skills and abilities as the more important motivator . Consistent with previous studies in Malaysia, the pharmacists in this study reported that salary was the major motivator and pointed out the absence of a performance‐based salary and promotion system.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…While pharmacists in New Zealand and Romania emphasized the importance of a higher salary as an important motivator, the pharmacists in Australia and the USA valued task assignment based on one’s skills and abilities as the more important motivator . Consistent with previous studies in Malaysia, the pharmacists in this study reported that salary was the major motivator and pointed out the absence of a performance‐based salary and promotion system.…”
Section: Discussionsupporting
confidence: 83%
“…The impact of such training on improving professional skills and work performance was previously demonstrated among the employees in the USA and European countries . Pharmacists in Romania reported a low level of job satisfaction and performance due to limited clinical training opportunities . Emergence of a similar situation in Malaysia is thus of concern, as the lack of opportunities for career training and self‐advancement may demotivate the pharmacists in the public healthcare system …”
Section: Discussionmentioning
confidence: 99%
“…This self-evaluation of their dietary behaviors doubled by the knowledge in drug’s component could be a reason for a self-administration of medicines. This habit was identified among medical students by a lot of researches focusing on this population [ 31 , 32 ] and among working pharmacists, with or without presenting a chronic disease [ 33 , 34 ]. The rates of self-administration of dietary supplements among pharmacy students balanced in different studies between 20% in Japan [ 35 ] and 47% in USA [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…When asked about whether it was matching between their professional expertise and salary, most pharmacists (58.43%) thought their salary was relatively low, and the comprehensive score for professional wellbeing was only 6.27 out of 10 points. According to several pieces of previous research, there are three domains for job satisfaction scale: payment-promotion, managementinterpersonal relationship, and organization-communication [13]. Workload, stress, advancement opportunities, job security, autonomy, fairness in the workplace, relationship with supervisors and colleagues, work flexibility, and working atmosphere are factors contributing to pharmacists' job satisfaction [14].…”
Section: Self-evaluation Of the Pharmacistsmentioning
confidence: 99%